Nebivolol influence on cardiovascular system and kidneys in post-partum arterial hypertension - A. L. Vertkin; A. V. Barabashkina; O. N. Tkacheva; A. V. Vasilyeva; G. I. Kuntsevich; A. V. Lazarev; I. E. Mishina (Российский кардиологический журнал)
.